18F-FDG PET/CT Findings of Scrub Typhus. (October 2015) - Kim, Jahae; Kwon, Seong Young; Kang, Sae-Ryung; Cho, Sang-Geon; Song, Ho-Chun
Abstract : Abstract: Scrub typhus is an acute infectious disease caused by Orienta tsutsugamushi, which is clinically manifested by fever, generalized lymphadenopathy, diffuse myalgia, headache, maculopapular rash, and eschars at the site of chigger feedings. Diagnosis of scrub typhus requires compatible clinical features, history of exposure, and result of selorogic testing. In recent years, 18 F-FDG PET/CT is seen as having increasing potential for use in examination and management of patients with infectious or inflammatory disorders. This is a PET/CT case demonstrating scrub typhus in a patient without evidence of recurrence of thyroid papillary cancer.